Case for Earmarked Taxes : Theory and Example. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The earmarking (or setting aside) of revenues from various taxes for specific types of expenditure is a much maligned fiscal practice. The paper examines a number of theoretical arguments and institutional circumstances under which earmarking (even widespread earmarking) may be welfare enhancing. The paper also questions the criticism that earmarking seriously erodes budgetary efficiency, and draws on the experience of Colombia to demonstrate that the worst fears of critics do not necessarily come to pass.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet